STRATEGI PENGEMBANGAN PARIWISATA DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PROVINSI NUSA TENGGARA TIMUR: Studi Kasus Kawasan Wisata Di Kabupaten Manggarai Barat - David Stevanus Gustiano Hake (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2024)
Indonesia is a country with abundant natural wealth, with natural beauty and diverse diversity, which is expected to be able to increase the Regional Original Income (PAD) of a province. West Manggarai Regency is one of the districts in East Nusa Tenggara Province which has promising potential to contribute to the Regional Original Income (PAD) of East Nusa Tenggara Province. This research aims to determine the optimal strategy for developing tourist attraction areas in West Manggarai Regency, so that the tourism sector in West Manggarai Regency can be managed and utilized optimally. After being analyzed by the author, the tourism sector in Manggarai Regency still has several obstacles in the field, namely related to several tourist assets in West Manggarai Regency which are still subject to illegal levies and the lack of local community involvement in the maintenance and exploration of tourist destinations in West Manggarai Regency, as well as a lack of cooperation. between related regions in the development and supervision of tourist attractions. To describe the situation in the field and then study and investigate it to find solutions to general problems, this research uses qualitative methods with a descriptive approach with SWOT analyze. The data used in this research regarding tourism development techniques to increase local revenue (PAD) was taken from the previous edition of Pustaka magazine as well as the consequences in choosing actions to be taken by the Tourism Office of West Manggarai Regency, East Nusa Tenggara Province.